Anti-GBM disease with a mild relapsing course and low levels of anti-GBM autoantibodies - Segelmark, Mårten (Clin Kidney J, 2012)
Anti-glomerular basement membrane disease (anti-GBM) is usually characterized by rapidly progressive glomerulonephritis, and when autoantibody production has ceased, relapses are rare. Here, we report a 71-year-old women diagnosed at a stage of mild renal insufficiency. Over a period of 10 years, she experienced three mild relapses with return of anti-GBM antibodies, haematuria and slight elevations in serum creatinine level. All three relapses responded to immunosuppressive therapy, and all were preceded by peaks of myeloperoxidase-antineutrophil cytoplasm antibodies (MPO-ANCA). This case shows that long-term follow-up is warranted in patients treated for anti-GBM-mediated disease, but urinary dipsticks may be sufficient for early detection of relapses.